Adherence to Contact Precautions Among Different Categories of Healthcare Workers Through Video Monitoring in a Tertiary Hospital Facility. (4th October 2017) - Katanami, Yuichi; Hayakawa, Kayoko; Sugiki, Yuko; Takaya, Saho; Yamamoto, Kei; Kutsuna, Satoshi; Takeshita, Nozomi; Kanagawa, Shuzo; Ohmagari, Norio
Abstract: Background: Contact precautions are required to prevent transmission of multidrug-resistant organisms; however, reports on adherence rates vary. Through video monitoring, we evaluated the adherence to the use of personal protective equipment (PPE) among different categories of healthcare workers. Methods: This study was conducted in a 781-bed tertiary hospital facility from June 2016 through March 2017. We installed cameras in areas where staff don PPE. Infection control team members observed the video and assessed adherence rates. Results: We noted 1, 073 opportunities for donning PPE. Rates of adherence to appropriate PPE use was 34%; it was significantly higher in infectious disease doctors (18/18, 100%) and cleaning staff (42/49, 86%) than in other groups ( P < 0.001 for both) (Table 1). Nurses had the most opportunities, but their adherence was inadequate (239/858, 28%). Adherence rates did not vary based on indications for precautions, with exceptions for Clostridium difficile (CD) infection and travelers' diarrhea (TD), where greater adherence was observed ( P = 0.044, P = 0.007, respectively). Conclusion: Adherence to contact precautions varied by occupation; however, overall adherence was insufficient. The lower adherence rate in nurses compared with other occupations might be due to more frequent visits for care. Disclosures: All authors: No reported disclosures.